Antioxidation copper slurry sintered in air and preparation method thereof
By coating nanographite powder on the surfaces of nanocopper powder and glass powder, rapid heating is used to utilize the thermal and electrical conductivity of graphite, the oxidation problem of nanocopper paste during sintering in the air is solved, and the mechanical strength and electrical conductivity after sintering are improved. Performance, achieving short sintering time and low resistivity.
Patent Information
- Application Number
- CN202410560081.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-05-08
AI Technical Summary
The existing nanocopper slurry is easily oxidized when sintered in air, which is difficult to sinter, and the mechanical strength and electrical properties after sintering are poor.
Using nanographite powder as the loading material for antioxidant components, nanographite slurry is coated on the surface of nanocopper powder and glass powder, and the thermal and electrical conductivity of graphite is used for rapid heating, and during the decomposition process of isopropanolamine A high-strength sintered structure is formed.
It improves the mechanical strength and conductivity after sintering, shortens the sintering time, and has low resistivity, which has good application prospects.
Smart Images

Figure BDA0004827411570000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power device interconnection materials, and in particular to an anti-oxidation copper slurry sintered in air and a preparation method thereof. Background Art
[0002] Low-temperature sintering technology of electronic paste is a hot topic in electronic packaging. Its sintering performance, conductivity, mechanical properties, etc. will have a significant impact on the performance of power devices. Nano copper paste uses nano copper powder as the conductive phase. It has the advantages of low price and high sintering connection strength. However, copper paste is easily oxidized when sintered in air and is difficult to sinter.
[0003] In the prior art, nano copper powder is generally treated on the surface to improve its antioxidant ability during the sintering process. Although these surface treatment agents have formed good antioxidant properties for the copper powder, these surface treatment components will volatilize during the sintering process. The pore structure formed after volatilization makes the mechanical strength of the sintered layer after sintering fail to reach the ideal structural strength. In addition, due to the existence of the surface coating structure, the surface treated copper slurry is difficult to sinter and the sintering time is long.
[0004] In order to overcome these defects, proposing an anti-oxidation copper slurry has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of this, the present invention proposes an anti-oxidation copper slurry sintered in air and a preparation method thereof. The copper slurry of the present invention aims to improve the mechanical strength of the slurry after sintering while maintaining good electrical properties.
[0006] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing an anti-oxidation copper slurry sintered in air, comprising the following steps:
[0007] Step 1, dispersing nano graphite powder in isopropanolamine, and obtaining nano graphite slurry after homogenization;
[0008] Step 2: Grind the nano copper powder and the glass powder evenly under a protective atmosphere to obtain a mixed powder;
[0009] Step 3: After mixing the nano-graphite slurry, the mixed powder and the dispersant, the mixture is homogenized and then degassed to obtain an antioxidant copper slurry sintered in air.
[0010] In some embodiments, the ratio of the average particle size of the nano-graphite powder to the average particle size of the nano-copper powder is 1:(5-10).
[0011] In some embodiments, the average particle size of the nano copper powder is 500-1500 nm, and the nano copper powder is spherical in shape.
[0012] In some embodiments, the nano-graphite powder has a flake-like morphology.
[0013] In some embodiments, the anti-oxidation copper slurry sintered in air includes, calculated by weight, 1-5 parts of nano graphite powder, 1-2 parts of isopropanolamine, 80-90 parts of nano copper powder, 10-15 parts of glass powder, and 1-5 parts of dispersant.
[0014] In some embodiments, in step 1, the speed of the homogenization treatment is 10000-15000 rpm, the pressure of the homogenization treatment is 10-15 MPa, and the time of the homogenization treatment is 5-10 min.
[0015] In some embodiments, in step 2, the grinding time is 20-30 min.
[0016] In some embodiments, in step three, the speed of the homogenization treatment is 5000-10000 rpm, the pressure of the homogenization treatment is 5-10 MPa, and the time of the homogenization treatment is 2-5 min.
[0017] In some embodiments, the dispersant is ethylene glycol or polyethylene glycol.
[0018] In some embodiments, the glass powder has an average particle size of 1-3 μm.
[0019] The second aspect of the present invention also provides a copper slurry obtained by repeatedly preparing the above-mentioned method.
[0020] The preparation method of the anti-oxidation copper slurry sintered in air of the present invention has the following advantages over the prior art:
[0021] Beneficial effects:
[0022] The method for preparing an anti-oxidation copper slurry sintered in air adopts nano-graphite powder as a loading material for an anti-oxidation component, and the nano-graphite slurry is coated on the surface of nano-copper powder and glass powder by preparing the nano-graphite slurry, and the pores between graphites in the graphite slurry are used to load isopropylamine, so as to achieve an anti-oxidation effect on the nano-copper powder. In addition, the graphite has good thermal conductivity, electrical conductivity and a low thermal expansion coefficient, and can form a thermal bridge during the sintering process to quickly heat the nano-copper powder. At the same time, good electrical conductivity can be provided after sintering. In the decomposition process of isopropylamine, the porosity between the graphite powders is slightly affected, and the sintered structure has higher strength. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0025] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0026] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.
[0027] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0028] Example 1
[0029] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass, and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0030] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0031] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 10 MPa and a rotation speed of 10000 rpm for 10 min to obtain nano-graphite slurry;
[0032] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0033] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0034] Example 2
[0035] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 3 parts of nano-graphite powder, 2 parts of isopropanolamine, 85 parts of nano-copper powder, 12 parts of glass powder and 3 parts of polyethylene glycol, wherein the average particle size of the nano-copper powder is 1000nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 2μm.
[0036] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0037] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 12 MPa and a rotation speed of 12000 rpm for 12 min to obtain nano-graphite slurry;
[0038] Grind the nano copper powder and the glass powder in a nitrogen atmosphere for 25 minutes to obtain a mixed powder;
[0039] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 8 MPa and a rotation speed of 7000 rpm for 3 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0040] Example 3
[0041] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 5 parts of nano-graphite powder, 2 parts of isopropanolamine, 90 parts of nano-copper powder, 15 parts of glass powder and 5 parts of polyethylene glycol, wherein the average particle size of the nano-copper powder is 1500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 300nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 3μm.
[0042] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0043] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 15 MPa and a rotation speed of 15000 rpm for 5 min to obtain nano-graphite slurry;
[0044] Grind the nano copper powder and the glass powder in a nitrogen atmosphere for 30 minutes to obtain a mixed powder;
[0045] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 10 MPa and a rotation speed of 10000 rpm for 10 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0046] Example 4
[0047] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 200nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0048] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0049] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 10 MPa and a rotation speed of 10000 rpm for 10 min to obtain nano-graphite slurry;
[0050] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0051] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0052] Example 5
[0053] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is flaky, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0054] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0055] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 10 MPa and a rotation speed of 10000 rpm for 10 min to obtain nano-graphite slurry;
[0056] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0057] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0058] Example 6
[0059] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is granular, and the average particle size of the glass powder is 1μm.
[0060] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0061] First, nano-graphite powder was mixed with isopropanolamine, and homogenized in a homogenizer at 10 MPa and a rotation speed of 10000 rpm for 10 min to obtain nano-graphite slurry;
[0062] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0063] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0064] Comparative Example 1
[0065] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass, and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0066] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0067] Nano-graphite powder, isopropyl alcohol, glass powder, nano-copper powder and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0068] Comparative Example 2
[0069] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass and are prepared from 1 part of isopropanolamine, 80 parts of nano copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano copper powder is 500nm, the nano copper powder is spherical, the average particle size of the nano graphite powder is 100nm, the nano graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0070] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0071] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0072] The mixed powder, isopropanolamine and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0073] Comparative Example 3
[0074] The raw materials of the antioxidant copper slurry sintered in the air of this embodiment are calculated by mass, and are prepared from 1 part of nano-graphite powder, 1 part of isopropanolamine, 80 parts of nano-copper powder, 10 parts of glass powder and 1 part of polyethylene glycol, wherein the average particle size of the nano-copper powder is 500nm, the nano-copper powder is spherical, the average particle size of the nano-graphite powder is 100nm, the nano-graphite powder is flaky, and the average particle size of the glass powder is 1μm.
[0075] The preparation method of the above-mentioned anti-oxidation copper slurry sintered in air is carried out according to the following steps:
[0076] First, nano-graphite powder is mixed with isopropanolamine, and the mixture is stirred and mixed in a stirring device at a speed of 1000 rpm for 10 minutes to obtain nano-graphite slurry;
[0077] Grind the nano copper powder and glass powder in a nitrogen atmosphere for 20 minutes to obtain a mixed powder;
[0078] The mixed powder, nano-graphite slurry and polyethylene glycol were mixed, homogenized in a homogenizer at 5 MPa and a rotation speed of 5000 rpm for 5 minutes, and then vacuum degassing was performed for 10 minutes to obtain an antioxidant copper slurry sintered in air.
[0079] The copper slurries prepared in the above examples and comparative examples were tested for their performance:
[0080] (1) Shear strength test:
[0081] The copper paste is printed on the surface of the ceramic copper-clad laminate by steel screen printing. The steel screen opening parameters are 2mm*2mm*100μm. After printing, it is dried at 140℃ in a nitrogen atmosphere for 20 minutes. After drying, a silver-backed silicon wafer is mounted on the surface of the paste layer, and then sintered at 250℃ and 20MPa for 10 minutes. The prepared interconnection joint is sheared in a push-pull dynamometer with a shear height of 15μm and a shear speed of 30μm / min, and the shear strength data is recorded.
[0082] (2) Thermal conductivity test:
[0083] The copper paste was printed on the surface of the ceramic substrate through a special mold, and the mold opening parameters were r = 5mm, h = 0.8mm. After printing, it was dried at 140℃ in a nitrogen atmosphere for 20 minutes. After drying, the ceramic substrate was covered on the surface of the paste layer, and then sintered at 250℃ and 20MPa for 10 minutes to obtain a sheet sample. The thermal diffusion coefficient of the sample was detected using the laser flash method. The test temperature was room temperature and the pulse width was 20μs. The specific heat capacity and density of the sample were measured, and the thermal conductivity was calculated and recorded.
[0084] (3) Resistivity test:
[0085] The copper paste is printed on the surface of the ceramic substrate through a special mold, and the mold opening parameters are r = 5mm, h = 0.8mm. After printing, it is dried at 140℃ in a nitrogen atmosphere for 20 minutes. After drying, the ceramic substrate is covered on the surface of the paste layer, and then sintered at 250℃ and 20MPa for 10 minutes to obtain a sheet sample. The resistance of the sheet sample is tested using the four-probe method, the test temperature is room temperature, and then the resistivity is calculated.
[0086] (4) Sintering time test:
[0087] Fill the copper slurry into the sintering mold to ensure that the sample is filled evenly. The mold cavity size is 2mm*2mm*100μm. Sinter at 250℃ and 20MPa. Observe the changes in sample color, shape and size, and record the sintering endpoint time.
[0088] The above test results are shown in the following table:
[0089]
[0090] It can be seen from the above example data that the copper slurry prepared by the preparation method of the present invention has good shear strength and short sintering time, low resistivity, good thermal conductivity, and has good application prospects.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an anti-oxidation copper slurry sintered in air, characterized in that: The steps include: Step 1, dispersing nano graphite powder in isopropanolamine, and obtaining nano graphite slurry after homogenization; Step 2: Grind the nano copper powder and the glass powder evenly under a protective atmosphere to obtain a mixed powder; Step 3, after mixing the nano-graphite slurry, the mixed powder and the dispersant, homogenizing and degassing to obtain an antioxidant copper slurry sintered in air; The ratio of the average particle size of nano-graphite powder to the average particle size of nano-copper powder is 1: (5-10), the average particle size of nano-copper powder is 500-1500nm, the average particle size of glass powder is 1-3μm, the morphology of nano-copper powder is flaky, and the nano-graphite powder is flaky. Calculated by mass, Sister Sha's antioxidant copper slurry in the air includes: 1-5 parts of nano-graphite powder, 1-2 parts of isopropanolamine, 80-90 parts of nano-copper powder, 10-15 parts of glass powder, and 1-5 parts of dispersant.
2. The method for preparing the anti-oxidation copper slurry sintered in air according to claim 1, characterized in that: In step 2, the grinding time is 20-30 minutes.
3. The method for preparing the anti-oxidation copper slurry sintered in air according to claim 1, characterized in that: In step 3, the speed of the homogenization treatment is 5000-10000 rpm, the pressure of the homogenization treatment is 5-10 MPa, and the time of the homogenization treatment is 2-5 min.
4. The method for preparing an oxidation-resistant copper slurry sintered in air according to claim 1, characterized in that: The dispersant is ethylene glycol or polyethylene glycol.
5. An anti-oxidation copper slurry sintered in air, characterized in that: The preparation method is described in any one of claims 1 to 4.
